Does the Exposure to Content of the Humor Videos Reduce Stress of College Students during Pandemic? - Chaidar, Erika; Silvia, Febriana Raya; Jatnika, Ratna (Penerbit Goodwood, 2023)
Purpose: The coronavirus disease (COVID-19) pandemic has created a global crisis that has drastically impacted the changing living conditions that cause stress. The general public has begun to use humor as a coping mechanism in dealing with a pandemic. Experiments were carried out with the aim of observing the effect of humorous displays on stress reduction. Methodology: Participants are the first-year college students who are selected using the samples in this study is a probability sampling technique, namely a simple random sampling. The research approach was a pre-post experimental design using stress measurement during the pandemic, namely the Covid Stress Scale (CSS). Data were analyzed by performing different tests on CSS scores before and after treatment. Results: The analysis results showed that there was a difference in the CSS score before and after treatment. Based on these data, it can be concluded that humorous impressions have an effect on reducing stress during a pandemic. Conclusions: The study concludes that exposure to humorous videos significantly reduces pandemic-related stress, supporting humor as an effective coping strategy that lowers stress hormones and promotes emotional resilience. Limitations: The experiment was conducted online. Contribution: This research offers college students an accessible way to reduce stress through humor, especially by watching humorous videos.